칼슘제, 피막제, GA 4+7 + BA의 수체살포 및 봉지씌우기에 의한 ‘감홍’ 사과의 동녹 방지와 과실품질 - 문영지(Young-Ji Moon); 남기웅(Ki-Woong Nam); 강인규(In-Kyu Kang); 문병우(Byung-Woo Moon) (Weon'ye gwahag gi'sulji, 2016)
This study was conducted to examine the effect of 0.4% of $CaCl_2$, $2H_2O$, $1mg{·}L^{-1}$ of Calmodulin (CaM)-SH, 250-folds of coating agent (WE-36), 1,000-folds of $GA_{4+7}+BA$ and 3 types of paper bagging treatments on russet incidence and fruit quality attributes of 'Gamhong' apple. The pattern of russet occurrence was slightly different for 4 years (from 2012 to 2015) in 'Gamhong' apple. The russet occurrence was lowest in $GA_{4+7}+BA$ treatment at 20 days after full bloom (DAFB), compared with other treatments. The $GA_{4+7}+BA$ treatment increased fruit weight at 20 DAFB, while the other fruit quality attributes were not influenced. The russet occurrence was lower not only in a single bag application than in untreated ones but also in yellow bagging and discolored bagging applications than in a white bagging application. The russet occurrence in a bagging application was lower at 20 DAFB than at 30 and 40 DAFB, while fruit quality attributes were not affected by bagging applications. The russet incidence was lower in $GA_{4+7}+BA$ twice treatments at 20 and 30 DAFB, and calcium coated bag at 30 DAFB after $GA_{4+7}+BA$ treatment at 20 DAFB than in untreated fruit. The rate of russet incidence was lowest at equator region in $GA_{4+7}+BA$ treatment, compared with the other fruit regions. Overall, the results suggest that one and/or two applications of $GA_{4+7}+BA$ (1,000-folds) treatment at 20 DAFB should reduce the risk of russet incidence in 'Gamhong' fruit. 본 연구는 칼슘제, 피막제, $GA_{4+7}+BA$의 수체살포 및 봉지씌우기 처리가 감홍 품종의 동녹 방지와 과실품질에 미치는 영향을 검토하기 위하여 실시하였다. 4년간(2012-2015)의 '감홍' 사과의 동녹 발생은 연도에 따라 차이가 있었으며 칼슘제, 피막제 및 $GA_{4+7}+BA$ 처리에 의한 동녹 발생 정도는 다른 처리에 비하여 만개 후 20일에 $GA_{4+7}+BA$ 1,000배액 처리구에서 현저하게 낮았고, 수확 시 과실 품질에는 큰 차이는 없었으나 과중은 증가하였다. 1중 봉지색 종류에 의한 동녹 발생정도는 무처리에 비하여 낮았고, 황색봉지 및 변색봉지 처리에서 우수하였다. 봉지씌우기 시기에 의한 동녹 발생정도는 만개 후 20일 처리가 만개 후 30, 40일 처리에 비하여 현저하게 낮았으며, 과실 품질에는 차이는 없었다. 그리고 $GA_{4+7}+BA$를 만개 후 20일과 30일에 2회 처리와 $GA_{4+7}+BA$을 만개 후 20일에 처리한 후 만개 30일에 칼슘함유봉지를 처리한 과실에 동녹발생이 각각 1.8과 1.3으로 무처리구(5.5)에 비하여 현저히 낮았다. $GA_{4+7}+BA$ 처리에 의한 과실부위별 동녹 발생 정도는 과실 과병부와 과정부에 비하여 과실의 중앙부에서 더 낮은 결과를 보였다. 따라서 '감홍' 사과의 동녹발생 경감을 위해서는 만개 후 20일에 $GA_{4+7}+BA$ 1,000배액 1회 및 2회 처리가 가장 우수한 효과를 나타내었다.